2019
DOI: 10.1016/j.jclinepi.2019.05.033
|View full text |Cite
|
Sign up to set email alerts
|

Single pivotal trials with few corroborating characteristics were used for FDA approval of cancer therapies

Abstract: Introduction: Novel cancer therapies are often approved with evidence from a single pivotal trial alone. There are concerns about the credibility of this evidence. Higher validity may be indicated by five methodological and statistical characteristics of pivotal trial evidence that were described by the US Food and Drug Administration (FDA) which may corroborate the reliance on a single trial alone for approval decisions.Methods: We did a meta-epidemiologic evaluation of all single pivotal trials supporting FD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…A meta-epidemiologic study published in 2019 evaluated all single-arm studies used for FDA approvals and demonstrated that the number of single-arm studies leading to approval increased substantially. Furthermore, the majority was based on studies with small sample sizes, and did not provide any other verifying studies (17). Recently, the EMA and FDA have been increasing the number of approvals based on non-randomized trials.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-epidemiologic study published in 2019 evaluated all single-arm studies used for FDA approvals and demonstrated that the number of single-arm studies leading to approval increased substantially. Furthermore, the majority was based on studies with small sample sizes, and did not provide any other verifying studies (17). Recently, the EMA and FDA have been increasing the number of approvals based on non-randomized trials.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12][13] On the other hand, healthcare professionals doi: 10.1136/bmj.n450 | BMJ 2021;372:n450 | the bmj collecting routine data during usual care might have more clinical expertise than research staff who often collect trial data only for a narrow time frame and scope, sometimes only for a few participants or even a single patient in each centre. 14 Since routine data are collected independently of the trial from people unaware of treatment allocations, biases related to outcome ascertainment might be even less likely than in traditional trials. Moreover, quality of routinely collected data can vary enormously for different outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…The main variables were grouped into the following binary categories: RCT (blinded and open-label) vs single-arm; surrogate outcomes (OvRR, ORR and PFS) vs overall survival; sample sizes of�200 vs <200 (following Ladanie et al, 2019 [18] recommendations); and magnitude of effect as large vs not large. Study characteristics were compared between accelerated…”
Section: Discussionmentioning
confidence: 99%
“…The main variables were grouped into the following binary categories: RCT (blinded and open-label) vs single-arm; surrogate outcomes (OvRR, ORR and PFS) vs overall survival; sample sizes of≥200 vs <200 (following Ladanie et al, 2019 [ 18 ] recommendations); and magnitude of effect as large vs not large. Study characteristics were compared between accelerated and regular approvals and this analysis was repeated for BTD for approvals from 2012 onwards, comparing BTD vs non-BTD, the absolute number and percentage was presented.…”
Section: Methodsmentioning
confidence: 99%